Discovery of soft and hard X-ray time lags in low-mass AGNs. Issue 3 (5th March 2021) - Mallick, L; Wilkins, D R; Alston, W N; Markowitz, A; De Marco, B; Parker, M L; Lohfink, A M; Stalin, C S
ABSTRACT: The scaling relations between the black hole (BH) mass and soft lag properties for both active galactic nuclei (AGNs) and BH X-ray binaries (BHXRBs) suggest the same underlying physical mechanism at work in accreting BH systems spanning a broad range of mass. However, the low-mass end of AGNs has never been explored in detail. In this work, we extend the existing scaling relations to lower mass AGNs, which serve as anchors between the normal-mass AGNs and BHXRBs. For this purpose, we construct a sample of low-mass AGNs ($M_{\rm BH}\lt 3× 10^{6} \, M_{\odot }$ ) from the XMM–Newton archive and measure frequency-resolved time-delays between the soft (0.3–1 keV) and hard (1–4 keV) X-ray emissions. We report that the soft band lags behind the hard band emission at high frequencies ∼[1.3−2.6] × 10 −3 Hz, which is interpreted as a sign of reverberation from the inner accretion disc in response to the direct coronal emission. At low frequencies (∼[3−8] × 10 −4 Hz), the hard-band lags behind the soft-band variations, which we explain in the context of the inward propagation of luminosity fluctuations through the corona. Assuming a lamppost geometry for the corona, we find that the X-ray source of the sample extends at an average height and radius of ∼10 r g and ∼6 r g, respectively. Our results confirm that the scaling relations between the BH mass and soft lag amplitude/frequency derived for higher mass AGNs can safely extrapolate to lower mass AGNs, and the accretion process is indeed independent of the BH mass.